Literature Review: Analysis Of Incompleteness of Filling in Medical Records Data in Hospitals - KHOTIMAH, SITI NUR; LAILIYAH, SYIFAUL (Universitas Hang Tuah, 2024)
Background: Analysis of incomplete filling of medical record information is needed to identify incomplete filling of patient cards in hospitals. Health information can be considered complete if the physician has filled in complete patient information within 1 x 24 hours after providing inpatient or outpatient services. Purposes: This study aims to determine incompleteness in filling hospital medical records and determine the factors that influence incomplete patient information in hospitals. Methods: Literature review with a comprehensive strategy via the internet using PRISMA. Literature was searched via Google Scholar with a publication year range of 2018-2023. Results: Several hospitals in Indonesia still have incomplete patient records. The incompleteness of hospital medical records in the study was shown in percentages of 59.48%, 17.40%, 42.4%, 7.66% and 15.7%. Factors of incomplete medical records in terms of 5M (Man, Machine, Method, Material, Money) Conclusions: Incompleteness of medical records is caused by a lack of knowledge, motivation and awareness of medical record managers. Discussion forums are not held in the form of meetings to discuss evaluation and follow-up as well as sanctions for officials who do not provide complete patient information. Lack of social skills when filling out medical records, unsystematic arrangement of medical record forms, and limited availability of funds.